CLINICAL OUTCOMES OF ENDOVASCULAR INTERVENTIONS IN DIABETIC PATIENTS WITH CRITICAL LOWER LIMB ISCHEMIA - I. A. Bondar («REMEDIUM GROUP» Ltd., 2019)
The article describes the features of lower limb vessel lesions in patients with diabetes, modern methods for diagnosing critical lower limb ischemia (CLLI), indications for endovascular interventions, and reviews the clinical outcomes of percutaneous transluminal balloon angioplasty in patients with diabetes. The authors emphasized high efficacy of endovascular operations in CLI in patients with diabetes. The issues of the prevention of CLLI and the treatment of the lower limb vascular diseases in diabetes are discussed.